In vitro study: thymoquinone inhibits the proliferation and migration of keloid fibroblasts and increases their apoptosis - Hadi, Restu Syamsul; Juniarti, Juniarti (MEDISAINS, 2025)
Background: No treatment can eliminate keloids. Thymoquinone (TQ) is hypothesized to play a pivotal role in treating keloids by modulating cellular processes such as proliferation, migration, and apoptosis. However, the existing studies investigating its effects on these mechanisms in keloid fibroblasts are limited and require further exploration.Objective: This study aims to investigate the effects of TQ on the proliferation, migration, and apoptosis of keloid fibroblasts in vitro.Methods: This experimental study was conducted using keloid fibroblast cultured in vitro. Cells were seeded in a 96-well plate at a density of about 5x103 cells per well with 100 μl of culture medium, and cells were cultured for 24, 48, and 72 hr for each concentration of TQ. Cell proliferation was assessed using a CCK-8 Kit, measuring optical density with a microplate reader. Apoptosis was measured using the TUNEL assay. Cell migration following TQ treatment was evaluated using the Scratch assay. The statistical test used a one-way analysis of variance (ANOVA) followed by the least significant difference (LSD) test. Results: TQ inhibited the proliferation of keloid fibroblasts at a dose of 5 µM after 48 hours of incubation and 10 µM after 24 hours of incubation. The inhibitory effect of TQ on fibroblast proliferation increased in a dose- and time-dependent manner. Treatment at 5 and 10 µM doses increased apoptosis in keloid fibroblast cultures. The TQ5 µM group achieved 60% closure, while the 10 µM group showed 55% closure. Migration was significantly inhibited in the 25 µM and 50 µM groups, with only 30% and 10% closure, respectively, at 72 hours.Conclusion: Thymoquinone inhibits the proliferation and migration of keloid fibroblast cells while promoting apoptosis. These properties suggest that TQ could be developed as a potential treatment for keloid-related skin issues.